Exclusive Breastfeeding as a Shield: Its Impact on Illness Incidence Among Infants Aged 6–12 Months at Kendalsari Health Center, Malang - Safitri, Dhea Ayu; Prastiwi, Swito; Yudianti, Ika (Women, Midwives and Midwifery, 2025)
Background: Illness is a state in which the body physically, mentally, and socially experiences weakness, disability, and discomfort. Newborn babies are more susceptible to disease because the antibodies in their bodies are not yet fully formed. Breast milk is the first intake to help the formation of the immune system because breast milk contains antibodies and other protective substances. Purpose: To determine the relationship between exclusive breastfeeding and the incidence of illness in infants aged 6-12 months at Kendalsari Health Center, Malang City. Methods: This study used a case control design with a retrospective approach. The sampling technique used purposive sampling. The sample in this study consisted of a case group (sick babies) as many as 35 mothers & babies in the Kendalsari Community Health Center MTBS Clinic and a control group (healthy babies) as many as 35 mothers & babies in Jatimulyo Village in March-April 2024. Results: The results of the Chi-square test value of exclusive breastfeeding with the incidence of illness obtained a significant p-value of 0.001 (<0.05). Conclusion: Exclusive breastfeeding has a significant effect on the incidence of illness in infants aged 6-12 months. Thus, it is expected that mothers can provide exclusive breastfeeding for infants aged 0-6 months. Future research can examine other factors (maternal condition, maternal psychology, and environment) that can affect exclusive breastfeeding and the incidence of illness.